Wetting and Phase Separation in the presence of Elasticity and Crystallization - Giso, Mathew. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Physics.; Advisor: Timothy Atherton.; Keyword: Condensed matter physics.